2022
DOI: 10.31219/osf.io/ej5y3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ecological meanings: A consensus paper on individual differences and contextual influences in embodied language

Abstract: Embodied theories of cognition consider many aspects of language and other cognitive domains as the result of sensory and motor processes. In this view, the appraisal and the use of concepts are based on mechanisms of simulation grounded on prior sensorimotor experiences. Even though these theories continue receiving attention and support, increasing evidence indicates the need to consider the flexible nature of the simulation process, and to accordingly refine embodied accounts. In this consensus paper, we di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 229 publications
1
8
0
Order By: Relevance
“…Our findings also contribute to research highlighting the role of context in mental simulation (Hoenig et al, 2008;Ibañez et al, 2022;Lebois et al, 2015;van Dam et al, 2012;Zwaan, 2014), and show for the first time that context can also affect sensory modality ratings, which is important to keep in mind for future research. Comparing Studies 1 and 2, we found the relationship between healthiness and perceptual ratings differed depending on whether or not food words were presented alone and referred to as "food words" (Study 2) or were presented with words from other semantic categories (Study 1, which used the Lancaster Norms; Lynott et al, 2020).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our findings also contribute to research highlighting the role of context in mental simulation (Hoenig et al, 2008;Ibañez et al, 2022;Lebois et al, 2015;van Dam et al, 2012;Zwaan, 2014), and show for the first time that context can also affect sensory modality ratings, which is important to keep in mind for future research. Comparing Studies 1 and 2, we found the relationship between healthiness and perceptual ratings differed depending on whether or not food words were presented alone and referred to as "food words" (Study 2) or were presented with words from other semantic categories (Study 1, which used the Lancaster Norms; Lynott et al, 2020).…”
Section: Discussionsupporting
confidence: 72%
“…A second goal of Study 2 was to explore the effect of context on mental simulation for food concepts, specifically in terms of situatedness. Previous work has shown the degree of mental simulation can be affected by the context in which a word is presented (Hoenig et al, 2008; van Dam et al, 2012; Zwaan, 2014; see also Ibañez et al, 2022). For example, a concept like hammer is more likely to engage action simulations if the context focuses on action-related meaning (Hoenig et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some limitations to consider when drawing conclusions from our results. First, we did not systematically investigate whether individual differences such as gender or motor expertise (e.g., athlete or dancer) might be related to the effects we observed in this study, and there is evidence of individual differences being related to sensorimotor effects in language processing ( Ibanez et al, 2022 ) and in body-object interaction effects in particular ( Muraki and Pexman, 2021 ). Therefore, some caution should be used when considering the generalizability of these findings.…”
Section: Discussionmentioning
confidence: 95%
“…This is demonstrated, for example, through activation in the brain's perceptual systems during language comprehension (e.g., Pulvermuller & Hauk, 2005;Simmons et al, 2007). While debates continue about the exact nature and extent of mental simulation, and the conditions under which it occurs during language comprehension (see, e.g., Connell, 2019;Ibañez et al, 2022;Ostarek & Huettig, 2019), it is notable that the role perceptual information from the chemical senses-such as olfaction-plays in word meaning is significantly neglected in this field (Speed & Majid, 2019). Recent work suggests there may be greater difficulty grounding language in the sense of olfaction than in the dominant senses of vision and audition (Speed & Majid, 2018, 2019.…”
Section: Introductionmentioning
confidence: 99%